Regulatory Mechanisms Controlling Human Hepatocyte Nuclear Factor 4α Gene Expression - Hatzis, Pantelis (American Society for Microbiology, 2001)
Hepatocyte nuclear factor 4α (HNF-4α) (nuclear receptor 2A1) is an essential regulator of hepatocyte differentiation and function. Genetic and molecular evidence suggests that the tissue-restricted expression of HNF-4α is regulated mainly at the transcriptional level. As a step toward understanding the molecular mechanism involved in the transcriptional regulation of the human HNF-4α gene, we cloned and analyzed a 12.1-kb fragment of its upstream region. Major DNase I-hypersensitive sites were found at the proximal promoter, the first intron, and the more-upstream region comprising kb −6.5, −8.0, and −8.8. By the use of reporter constructs, we found that the proximal-promoter region was sufficient to drive high levels of hepatocyte-specific transcription in transient-transfection assays. DNase I footprint analysis and electrophoretic mobility shift experiments revealed binding sites for HNF-1α and -β, Sp-1, GATA-6, and HNF-6. High levels of HNF-4α promoter activity were dependent on the synergism between either HNF-1α and HNF-6 or HNF-1β and GATA-6, which implies that at least two alternative mechanisms may activate HNF-4α gene transcription. Chromatin immunoprecipitation experiments with human hepatoma cells showed stable association of HNF-1α, HNF-6, Sp-1, and COUP-TFII with the promoter. The last factor acts as a repressor via binding to a newly identified direct repeat 1 (DR-1) sequence of the human promoter, which is absent in the mouse homologue. We present evidence that this sequence is a bona fide retinoic acid response element and that HNF-4α expression is upregulated in vivo upon retinoic acid signaling.